An Analysis of the Management of the 'Tasbih' Hajj Savings Product at Bank Sumsel Babel Based on the Wadi’ah Principle in the Perspective of DSN-MUI Fatwa No. 02/DSN-MUI/IV/2000 - Rafika Aulia; Meydiah Astuti; Nova Rahmadaniarti (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2025)
Hajj savings is a Sharia-compliant financial product designed to facilitate Muslims in preparing for and financing the pilgrimage to Mecca. This product allows customers to open a special savings account, make an initial deposit, and settle the Hajj Travel Cost (BPIH). The funds in this account are not withdrawable at any time, but are subject to specific regulations. This study aims to analyze the management of the "Tasbih" (Tabungan Siap Beribadah Haji) savings product at Bank Sumsel Babel based on the wadi’ah principle, as outlined in the DSN-MUI Fatwa No. 02/DSN-MUI/IV/2000. The Tasbih product is a type of Hajj planning savings account that uses the wadi’ah yad dhamanah contract, which refers to a safekeeping agreement whereby the bank is permitted to utilize the deposited funds while guaranteeing full return to the customer. This study adopts a descriptive qualitative approach through literature review and interviews with relevant stakeholders at Bank Sumsel Babel. The findings indicate that the management of the Tasbih product complies with Sharia principles, particularly those stipulated in the aforementioned fatwa. While the bank does not promise bonuses, it voluntarily provides hibah (gifts) based on financial performance, and the customers' funds are managed with integrity and trust. Thus, the Tasbih savings product is deemed to fulfill Sharia compliance and serves as a financial solution for individuals planning their Hajj journey in a gradual and well-organized manner.